Welding and metal fabrication - Jeffus, Larry F. (Clifton Park, NY : Delmar, 2012)
A welding and metalwork textbook combines the skills of measuring, cutting, shaping, fitting, welding, and finishing and includes hands-on exercises, experiments, and projects.
Introduction -- Welding safety -- Shop math -- Reading technical drawings -- Welding joint design, welding symbols -- Fabricating techniques and practices -- Welding shop practices -- Shielded metal arc equipment, setup, and operation -- Shielded metal arc welding place -- Shielded metal arc welding pipe -- Gas metal arc welding equipment and materials -- Gas metal arc welding -- Flux cored arc welding equipment and materials -- Flux cored arc welding -- Gas tungsten arc welding equipment and materials -- Gas tungsten arc welding -- Oxyfuel welding and cutting equipment, setup, and operation -- Oxyacetylene welding -- Soldering, brazing, and braze welding processes -- Soldering and brazing -- Oxyacetylene cutting -- Plasma arc cutting -- Arc cutting, gouging, and related cutting processes -- Other welding processes -- Welding automation and robotics -- Filler metal selection -- Welding metallurgy -- Weldability of metals -- Welder certification -- Testing and inspecting welds.
Includes index.
Keywords: Welding; Metal-work.; Welding; Metalwork